The economic effects of the general budget deficit on investment An applied study on the Syrian economy between the years - اسبر هدى (Latakia University Journal - Economic and Legal Sciences Series, 2023)
When the general budget is not just an accounting financial statement that presents the government’s plan and the results of its work, this means that it has evolved into a financial tool that generates economic and social effects that the government desires. This study seeks to verify this practically in Syria, by making an analytical presentation of the Syrian public budget, evaluating its expenditures and revenues, conducting accounts and its impact on investment. To achieve this, the study followed a scientific methodology that falls within the context of the descriptive analytical approach. It followed the statistical method: to prove hypotheses related to the relationship of the public budget deficit to investment. The study concluded that the deficit is an inherent state of the general budget, and that it has an impact on private investment through the integration of public spending with private investment and the negative tax impact on it. Likewise, there was a significant relationship with public investment. The study presented proposals that would activate the public budget deficit as a financial tool to stimulate investment.